The Role of Buddhist Teachers in Improving Students' Emotional Regulation - Novianti (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
Adolescents often have difficulty in overcoming and controlling the emotions they face, resulting in aggressive behaviour such as breaking rules, coming late, and behaviour that violates religious values ​​and norms. The study aims to describe the role of Buddhist religious teachers in improving students' emotional regulation abilities. The study employed a qualitative descriptive method, collecting data using purposive sampling techniques with informants, namely Buddhist religious teachers who teach in Wonogiri Regency to high school students. The results of the study showed that teachers have played a role in improving students' emotional regulation by directing students who behave aggressively to calm down, practicing meditation practices, namely regulating breathing in and out, motivating to behave well, being a good listener when students tell their problems, being patient, showing attention, and not getting tired of giving advice and motivation. The roles carried out include teachers as teachers, mentors, administrators, role models, motivators, and educators. Buddhist religious teachers have developed the competencies of a teacher as pedagogical, social, leadership, and professional competencies. Keywords: role, teacher, Buddhism, regulation, emotion